2018
DOI: 10.1101/324962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular dynamics simulations disclose early stages of the photo-activation of cryptochrome 4

Abstract: Birds appear to be equipped with a light-dependent, radical-pair-based magnetic compass that relies on truly quantum processes. While the identity of the sensory protein has remained speculative, cryptochrome 4 has recently been identified as the most auspicious candidate. Here, we report on allatom molecular dynamics (MD) simulations addressing the structural reorganisations that accompany the photoreduction of the flavin cofactor in a model of the European robin cryptochrome 4 (ErCry4). Extensive MD simulati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 76 publications
1
9
1
Order By: Relevance
“…S21, ESI†) accompanied by Trp decomposition and allowing FAD release. Consistent with our suggestion, in previous studies it was shown that absorption of light by DmCRY leads to conformational changes in the CTT, that were shown to be largely irreversible,4951 thus allowing the interaction with TIM followed by proteasomal degradation of both proteins. Further, we suggest that similar to animal type II CRY,53 the E3 ubiquitin ligase, Ramshackle,13 binds to the DmCRY FAD-binding pocket making the FAD release a requirement for subsequent ubiquitylation and its proteasomal degradation, thus, allowing the next cycle of the circadian clock (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…S21, ESI†) accompanied by Trp decomposition and allowing FAD release. Consistent with our suggestion, in previous studies it was shown that absorption of light by DmCRY leads to conformational changes in the CTT, that were shown to be largely irreversible,4951 thus allowing the interaction with TIM followed by proteasomal degradation of both proteins. Further, we suggest that similar to animal type II CRY,53 the E3 ubiquitin ligase, Ramshackle,13 binds to the DmCRY FAD-binding pocket making the FAD release a requirement for subsequent ubiquitylation and its proteasomal degradation, thus, allowing the next cycle of the circadian clock (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the nature of the involvement of the CTT diverges in the type IV CRYs, where an increase in proteolysis is not observed and the CTT rather may be protected in the light. Furthermore, in contrast to recent molecular dynamics simulations of Cl CRY4, crystal structures of WT and Y319D PHR domains confirm that His353 contacts the ribityl chain of FAD to enable type I-like protonation events to affect contacts to the CTT in the ground and/or signaling states (45, 53). Thus, based on limited proteolysis assays, the primary photochemical events mirror type I CRYs, in which initial formation of the semiquinone state of FAD could propagate to the FAD-binding cleft to alter the protonation state of a conserved His residue.…”
Section: Discussioncontrasting
confidence: 77%
“…The direction of the magnetic field influences, how much of the Cry goes back to the ground state and how much of the Cry is converted to a signalling state. This process probably leads to a conformational change in the C-terminus of Cry4 that is also observed in other Cry variants 18,20,[27][28][29] . This photo-excited Cry would then trigger a magneto-sensitive cell response via protein-protein interactions.…”
mentioning
confidence: 77%